Reading the Zoom Room: Union Negotiators’ Experience of Virtual Bargaining during COVID-19 - Foster, Jason (Labour / Le Travail, 2025)
One adaptation required by the covid-19 pandemic was a shift to virtual meetings. Collective bargaining has traditionally been conducted in person, but covid forced union and employer negotiators to adopt virtual forms of bargaining. This article examines union negotiators’ experiences with virtual bargaining in this period – first, to document the nature of the adaptations made during a historical public health event, and second, to determine whether either the shift to virtual bargaining or other covid restrictions undermined union bargaining power. It finds that the technical aspects of virtual bargaining did not significantly impact bargaining power, but broader challenges caused by covid did negatively impact union bargaining power at and away from the table.